Transformasi “Nongkrong” di Era Digital: Studi Kasus di Warkop Bandar Kupi Kota Medan - Prabhaswara, Muhammad Prakoso; Gustan, Gustan; Ginting, Rahmanita (Universitas Medan Area, 2025)
This study aims to understand how the digital era has transformed the way people